2008
DOI: 10.5507/bp.2008.008
|View full text |Cite
|
Sign up to set email alerts
|

Potential Diagnostic Markers in Nodular Lesions of the Thyroid Gland: An Immunohistochemical Study

Abstract: Aims:The diff erential diagnosis of thyroid nodules in routine practice can be problemmatic for both pathologists and clinicians. Eff ective treatment requires a determination of the biological nature of the lesions. For this reason, ancilliary diagnostic markers along with histological examination of the nodules may be useful. The objective of this study was to evaluate the diagnostic usefulness of novel markers in the diagnosis of hyperplastic and neoplastic nodules.Methods: Forty eight thyroid lesions formi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
(68 reference statements)
0
4
0
1
Order By: Relevance
“…An increase in MMP-2 cleaved galectin-3 protein correlated with angiogenesis in progressive stages of breast and prostate cancer (Nangia-Makker et al 2007Wang et al 2009). While galectin-3 is a diagnostic and/or prognostic marker for thyroid (Liu et al 2008;Rydlova et al 2008;Than et al 2008), gastric (Baldus et al 2000;Miyazaki et al 2002), colorectal cancer (Lu et al 2017) and to some extent pancreatic cancer (Shimamura et al 2002), melanocytes accumulate galectin-3 in the nucleus as the melanoma progresses (Prieto et al 2006). Nuclear galectin-3 expression in association with thyroid transcription factor 1 is an independent marker of worst prognosis for lung cancer patients (Puglisi et al 2004), whereas in colon cancer enhanced cytoplasmic levels of galectin-3 were reported (Lotz et al 1993;Sanjuan et al 1997).…”
Section: Galectin-3 As a Cancer Biomarker And Therapeutic Targetmentioning
confidence: 99%
“…An increase in MMP-2 cleaved galectin-3 protein correlated with angiogenesis in progressive stages of breast and prostate cancer (Nangia-Makker et al 2007Wang et al 2009). While galectin-3 is a diagnostic and/or prognostic marker for thyroid (Liu et al 2008;Rydlova et al 2008;Than et al 2008), gastric (Baldus et al 2000;Miyazaki et al 2002), colorectal cancer (Lu et al 2017) and to some extent pancreatic cancer (Shimamura et al 2002), melanocytes accumulate galectin-3 in the nucleus as the melanoma progresses (Prieto et al 2006). Nuclear galectin-3 expression in association with thyroid transcription factor 1 is an independent marker of worst prognosis for lung cancer patients (Puglisi et al 2004), whereas in colon cancer enhanced cytoplasmic levels of galectin-3 were reported (Lotz et al 1993;Sanjuan et al 1997).…”
Section: Galectin-3 As a Cancer Biomarker And Therapeutic Targetmentioning
confidence: 99%
“…Giatromanolaki et al [ 46 ] showed that FTCs displayed a higher vascular density, whereas subsequent research by Gulubova et al [ 26 ] suggested higher CD31 MVD in PTCs. However, several successive studies which applied either a CD34 or CD31 immunohistochemical marker for staining of the endothelium, could not identify a correlation between MVD and histology[ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 2) Papillary hyperplasia/hyperplastic nodule versus classical papillary carcinoma. 4 Hyperplastic nodules may sometimes mimic some histological features of papillary carcinoma. 5,6 In some cases of nodular goiter, the nuclear clearing and inclusions can be present in most of the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Also, intra-and inter-observer variation is a well-documented fact in thyroid pathology. [16][17][18] Thus, to overcome these difficulties, several workers have proposed different IHC markers, 4 such as, CK19, CK 903, CITED1, CD 26, CD 57, cyclin D1, cyclooxygenase-2, fibronectin-1, galectin-3, HBME-1, ki67, p27, p63, Ret oncoprotein, S 100, TPO and their efficacy in diagnosis, treatment and prognosis are being evaluated.…”
Section: Discussionmentioning
confidence: 99%